Pengembangan Media Pembelajaran PAI Berbasis Lingkungan melalui Model ASSURE - Hasan Baharun (Cendekia: Kependidikan dan Kemasyarakatan, 2016)
This paper presents the development of instructional media techniques based Islamic Religious Education in order to streamline the learning environment by ASSURE Model. The development of media-based learning environment is done in order to create learning conditions that attract Islamic education, not monotonous, not boring, and fosters the enthusiasm students to study harder. Learning based on the environment as part of contextual learning, giving students direct experience in interacting with the environment, such as; social environment, the natural environment and the built environment, so as to create more meaningful learning conditions for them and made possible the formation of personality and character of students, such as love of the environment.حاولت هذه المقالة عرض بعض الأساليب لتطوير الوسائل التعليمية لمادة التربية الإسلامية على أساس البيئة ليكون التدريس فعّالا على نموذج ASSURE. والتعليم أساسا هو عملية الاتصال بين المعلّم والمتعلّم للوصول إلى الأهداف المقرّرة. ولتكوين عملية الاتصال فعّالة يُحتاج إلى تطوير الوسائل التعليمية – وغيرها كذلك – على أساس البيئة في نموذج ASSURE. والهدف من هذا تكوين ظروف تعليم مادة التربية الإسلامية متمركزة في الطلاب، وتفعيل الطلاب وتمكينهم، وإزالة الرتيب والسآمة منهم، وغرس الحماسة وتقويتها في التعلّم. والتعليم على أساس البيئة نوع من التعليم السياقي، يعطى الطلاب الواقع العملي في التعامل مع عدة البيئات المحيطة بهم؛ البيئة الاجتماعية، والبيئة الطبيعية، والبيئة الاصطناعية حتى يقدروا على تكوين ظروف التعليم ذات معنى لهم حتّى تكوّنت في نفوس الطلاب شخصية قوية مثل حبّ البيئة.